- Pemanfaatan Hasil Panen Pekarangan Rumah Untuk Pembuatan Obat Tradisional Dan Bumbu Masakan Praktis Berbahan Dasar Bubuk Bawang Putih Lokal ‘Eban’ - Bani, Polikarpia Wilhelmina; Naisumu, Yolanda Getrudis; Binsasi, Remigius; Metboki, Bernadina; Purwantiningsih, Theresia Ika (Dewan Pimpinan Daerah (DPD) Perkumpulan Dosen Indonesia Semesta (DIS) Jawa Timur, 2022)
The harvest in Saenam Village is very abundant and its utilization is still low, so it is interesting to increase the benefit of the harvest from the yards of the local village community to be more useful and increase economic value in the the covid-19 pandemic situation. The harvest in Saenam Village is very abundant and its utilization is still low, so as a researcher I want to increase the utilization of the harvest from the yard of the local village community so that it is more useful and increases economic value in the midst of the COVID-19 pandemic situation. At the time of harvest, the price of garlic is very low, so processing garlic into powder can increase the value of its benefits and economic value. Garlic powder produced is not only a traditional medicine for humans, but also useful as an anti-bacterial for animals and anti-microbial and anti-pest for plants. This public service activities are welcome by the community. They are very enthusiastic about participating in this community service because their benefits harvest can increase through processing into garlic powder. The obtained garlic powder which is directly applied as an anti-pest for garlic plants that have not been harvested and as a practical cooking spice. Garlic powder as a practical cooking spice and traditional medicine is very effective to use because it saves time when cooking and saves costs in terms of disease treatment and plant pest control. In addition, it can improve the welfare of the people of Saenam Village. Garlic without being processed sold only twenty five thousand rupiah per kilogram. When that one kg is processed into powder and packaged, it will be sold at a price of five thousand – seventy five thousand per kilogram. The conclusion of this service is that the value of the garlic benefits can be increased through processing into powder.